2002
DOI: 10.1046/j.1445-5994.2002.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system prophylaxis in haematological malignancies

Abstract: Given the poor prognosis of central nervous system (CNS) involvement in haematological malignancies, management is directed towards prevention. CNS prophylaxis may take the form of intrathecal therapy, cranial irradiation, systemic therapy or some combination of these. The toxicity of these methods is an important consideration. A risk-orientated approach to the delivery of CNS prophylaxis in each disorder is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
(119 reference statements)
0
8
0
1
Order By: Relevance
“…Strategies to prevent CNS relapse include prophylactic IT chemotherapy, RT, systemic therapy, or a combination of these treatments (1). The Children’s Cancer Group showed that intensive chemotherapy with IT methotrexate during induction, consolidation, and delayed intensification was equivalent to whole brain RT (18 Gy) in preventing CNS relapse in children with ALL (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies to prevent CNS relapse include prophylactic IT chemotherapy, RT, systemic therapy, or a combination of these treatments (1). The Children’s Cancer Group showed that intensive chemotherapy with IT methotrexate during induction, consolidation, and delayed intensification was equivalent to whole brain RT (18 Gy) in preventing CNS relapse in children with ALL (16).…”
Section: Discussionmentioning
confidence: 99%
“…Leukemia involving the central nervous system (CNS) has traditionally resulted in a very poor prognosis, with efforts focused on preventing CNS relapse rather than treatment once relapse has occurred (1, 2). Without CNS prophylaxis, CNS involvement occurs in <5% of patients with acute myeloid leukemia (2) compared with 25% to 50% in patients with lymphoid leukemias.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, systemic therapy is associated with wide-spread toxicities. High-dose cytarabine is associated with liver dysfunction, cerebellar dysfunction, mucositis, diarrhea, rash, and fever [23]. High-dose methotrexate is associated with renal dysfunction, transient hepatitis, mucositis, and (rarely) neurotoxicity [24].…”
Section: Chemotherapymentioning
confidence: 99%
“…1 Although the natural history of leukemia/lymphoma has been known to include CNS disease, 2,3 recent advances in therapy leading to overall improved hematologic malignancy outcomes have increased the rates of patients presenting with this therapeutic challenge, primarily from poor CNS penetrance of cytotoxic and targeted therapy agents. 4,5 Although leukemia and lymphoma involving the CNS is generally associated with poor prognosis, 46 a prior study demonstrated that whole brain or craniospinal irradiation (CSI) still conferred a 12-month CNS progression-free survival rate of 77% in patients affected with acute leukemia. 1 With the continued discovery of novel chemotherapeutic and targeted regimens and improved survival rates for patients with hematologic malignancies, there is an increased focus on optimizing treatment toxicity profiles and patient quality of life, along with local and systemic disease control.…”
Section: Introductionmentioning
confidence: 99%